A Critical Study of Mukhannath's Law as a Homosexual Argumentation - Henri Shalahuddin; Syamsul Badi'; Cep Gilang Fikri Ash-Shufi (Media Syari'ah, 2021)
The term mukhannath in the study of Islamic law by Muslim feminists is considered to be the basis for the legitimacy of homosexual behavior. Muslim feminists present the meaning of mukhannath as behavior as well as sexual orientation that is permitted in Islam and in accordance with divine nature, so that homosexuality is a natural act in Islam and must be accepted as it is. On that basis, feminists distinguish homosexuality with liwath behavior that can be applied to homosexual, heterosexual and bisexual perpetrators. This is contrary to Islamic teachings/shari'a regarding the heresy of the Prophet Luth a.s who by the muslim scholars are called luthi, namely the perpetrators of liwath. Likewise, in interpreting mukhannath, the feminist framework is built from the concept of gender which is not derived from the treasures of Islamic scholarship or Islamic perspective. For this reason, the author tries to research and analyze the meaning and concept of mukhannath, and straighten it out according to the Islamic worldview. By using the descriptive-analytical method and using the literature as a database, the researchers came to the following conclusions; The meaning of mukhannath is the behavior of men who resemble women in terms of speech, gestures and clothing. This meaning does not recognize the difference between sexual orientation or behavior, but must be returned to the nature of its creation, namely its absolute gender. The muslim scholars have agreed that homosexual translation in Islam is liwath, which in the Qur'an is punished as destroying human nature (fitrah). The nature of creation (fitrah) must be in harmony with divine destiny which is eternal, as well as homosexual law in Islam is qath'i, not mutaghayyirah. For this reason, it is not appropriate if the gender analysis system is built on the basis of relatively social constructs used in the discussion of qath'i Islamic law.